English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Steps Please!

2007-03-18 06:17:48 · 3 answers · asked by akademiks28 1 in Science & Mathematics Mathematics

3 answers

♠ y(x)*dx = dx*(1-sin x)/cosx =dx/cosx –dx*sinx/cosx =y1*dx+y2*dx;
y1*dx= dx/cosx;
t=tan(x/2), dt=0.5dx/ (cos(x/2))^2 =0.5dx*(1+tt),
hence dx=2dt/(1+tt), cosx =(1-tt)/(1+tt); thus
♣ y1(t)*dt =2dt/(1-tt) =dt/(1-t) +dt/(1+t), hence
Y(t) = ln|(1+t)/(1-t)| =ln|(1+t)^2/(1-t^2)|;
Y(x) = ln|((cos(x/2))^2 +2cos(x/2)*sin(x/2) +(sin(x/2))^2)/
/((cos(x/2))^2 –(sin(x/2))^2) = ln|(1+sinx)/cosx|;
♦ y2(x)*dx =-dx*sinx/cosx =d(cosx)/cosx =d(ln|cosx|);
♥ Y(x) = ln|(1+sinx)/cosx| +ln|cosx| =ln|1+sinx| +C;
need more details? Click me!

2007-03-18 10:08:57 · answer #1 · answered by Anonymous · 1 0

∫(1-sin x)/cosx dx

distribute the 1/cos(x) to seperate it

∫1/cos(x) dx - ∫sin(x)/cos(x) dx

Simplify slightly
∫sec(x)dx - ∫tan(x)dx

Integrate
ln |sec(x) + tan(x)| - ln | sec(x) | + C

2007-03-18 13:40:25 · answer #2 · answered by radne0 5 · 0 0

Try breaking it up into two, 1/cos x and (sin x)/(cos x). And take it from there.

2007-03-18 13:21:06 · answer #3 · answered by Anonymous · 0 0

fedest.com, questions and answers